Sistem pengesanan bagasi menggunakan teknologi RFID bagi Haji dan Umrah “BAGTRAC” - Hassim, Nurul Farhanah (2009)
Lost baggage occured due to mishandled that leads to delayed, mismatch or misplace. This situation is getting worse when the baggage is mishandled and ends up at a location different from the owner’s destination. Bag Tracking System (BagTrac) is developed due to the complaints made by customers about the mishandled bags. Based on the current situation, it is done by manual system which necessitating additional time and expense for the carrier in finding and returning the baggage to the owners. Not only does lost baggage create poor relations between the organization and the customer, but also additional personnel and equipment are required in order to find lost baggage and return it to the proper owner. Therefore, BagTrac has come out with the solution by using the Radio Frequency Identification (RFID) technology to prevent the mishandled bags, to provide for locating-lost or disoriented bags and to help perform quick re-location of bags. Therefore, BagTrac is a needed for coordinating the efforts to handle bags and match claims with lost baggage and reduce the time by which lost bags are returned to rightful owners. The software used in designing and developing this system are Visual Basic Version 9.0 and Microsoft SQL Server 2008 for the database. The BagTrac System is proved to be effective in avoiding mishandled baggage.